Hubungan Pemberian MPASI Pada Bayi Usia 3-5 Bulan Dengan Kejadian Obesitas di Wilayah Desa Tanjung Gusta - Gultom, Mona Vebiyanti; Simatupang, Helmalia Alnesa; Nurlita, Ira; Gea, Jernihati; Siregar, Debi Novita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Obesity is a medical condition characterized by excessive fat accumulation that exceeds standard weight-for-height thresholds. One of the factors causing obesity is diet and nutritional intake, so obesity greatly affects children's growth and development. Globally, around 42 million children under five suffer from obesity, representing a major public health concern. One of the factors causing obesity in babies is early provision of MPASI. Objective: To find out whether MPASI at the age of 3-5 months is related to the incidence of obesity in the Tanjung Gusta Village Area. Method: This research uses a quantitative type of research with a cross sectional research design. This research uses data collection methods for measuring body weight (BB) and height (TB), as well as questionnaires which are filled out by respondents according to the instructions given. The type of data collected in this research is primary data obtained directly from respondents through a questionnaire which includes questions related to dependent and independent variables, as well as secondary data obtained by researchers indirectly through midwives in the Tanjung Gusta Village Area. Where researchers want to know the relationship between giving MP-ASI to babies 3-5 with the incidence of obesity in the Tanjung Gusta Village area. Results: It can be seen from the results of the chi-square correlation test of the relationship between giving MP-ASI to babies aged 3-5 months and the incidence of obesity in the Tanjung Gusta Village area. The test was carried out using the chi-square correlation test and obtained an Asymp Sig of 0.002 < 0 .05 means there is a relationship between giving MP-ASI to babies aged 3-5 months and the incidence of obesity in the Tanjung Gusta Village area.